Two new species of Distaplia (Tunicata: Ascidiacea) from the SW Atlantic, Argentina - Lagger, Cristian; Tatián, Marcos (Zootaxa, 2013)
The ascidian fauna from the Southwestern Atlantic(ArgentineSea) have scarcely been studied and have rarely been sampled. The existing scanty ascidian records are from specimens collected by dredging many decades ago. During samplings in the San Matias Gulf (Río Negro, Patagonia), two new Distaplia species were found. Distaplia naufragii sp. nov. was collected in the subtidal zone attached to a shipwreck, while the other species, Distaplia fortuita sp. nov. was found released by the tides in the sandy intertidal zone. These two new species differ deeply from each other in the size and morphology of their zooids. They represent one third of the known species belonging to the family Holozoidae in theSW Atlantic. These results reinforce the importance of new studies in this extensive but little explored area that is, in addition, susceptible to invasion by non-native species.